Synchronous recurrence of concurrent colon adenocarcinoma and dedifferentiated liposarcoma. Issue 5 (13th May 2019) - Jung, Eric E; Heinemann, F Scott; Egelston, Colt A; Wang, Jennifer; Pollock, Raphael E; Lee, Peter P; Tseng, William W
Abstract : A 62-year-old man presented with concurrent sigmoid colon adenocarcinoma and small bowel mesenteric dedifferentiated liposarcoma. Following surgical resection of the colon cancer, complete excision of the mesenteric sarcoma and adjuvant folinic acid, fluorouracil and oxaliplatin (FOLFOX) chemotherapy, the patient demonstrated no radiological evidence of disease for more than 2 years. The patient then developed synchronous recurrence of both cancers: the colon cancer metastasised to the liver and a pelvic lymph node, and the liposarcoma recurred in the original location. The patient underwent additional chemotherapy with complete response of the metastatic colon cancer and stable disease for the liposarcoma. The recurrent mesenteric tumour was subsequently resected. Although concurrent cancers have been reported, this unique case of synchronous recurrence raises interesting hypotheses regarding host–tumour interaction and immune surveillance.